Exploring Galleria mellonella as a novel model for evaluating permeation and toxicity of natural compounds - Samanta de Matos Silva; Junya de Lacorte Singulani; Lígia de Souza Fernandes; Ketylin Fernanda Migliato; Maria José Soares Mendes-Giannini; Ana Marisa Fusco-Almeida (Public Health and Toxicology)
Introduction Recent legislative advancements emphasize the need for alternative methods in assessing efficacy and safety while adhering to the 3Rs principles (reduce, replace, and refine) of animal experimentation. In this context, Galleria mellonella has become a well-established model in safety and efficacy research. However, existing studies predominantly focus on its use in injectable routes concerning pathogens and chemical compounds, leaving a significant gap in understanding other administration pathways, particularly topical application. To address this gap and contribute to the validation of G. mellonella as a model for cutaneous absorption studies, our investigation compares the toxicity data of gallic acid (GA) in mammalian models, alternative animal models such as G. mellonella and Caenorhabditis elegans, as well as monolayer cell cultures, providing insights valuable for future research.